Hello Victoria, (Xm , Ym) = ((x1+x2)/2, (y1+y2)/2) = ((7+-13)/2, (14+-6)/2) = ( -6/2, 8/2) = (-3,4)

Hello Victoria, (Xm , Ym) = ((x1+x2)/2, (y1+y2)/2) = ((7+-13)/2, (14+-6)/2) = ( -6/2, 8/2) = (-3,4)

when solving a quadratic equation by graphing, we find the roots using which of the following? (answer)

X-Intercept is the value of x where cross x axis. Another name is the zeros of the function, when y is zero, the graph cross the x-axis The answer is x-intercepts, Nataliya already answer the question. I just add some explanations to it.

|x+3|-3 > 1 Two case by replacing equal sign, a related equation. Case one x+3 -3-1 = 0 X-1 =0 X = 1 Case two -(x+3)-3-1 =0 -x -3-4 =0 -x-7 =0 -x = 7 x = -7 using a number line analysis: Check each interval (- infinity, -7], [-7, 1] and [1,...

Find the inverse Laplace transform? (answer)

Sol/ use a partial fractions to rewrite F(s)in a form. Please carefully watch the parentheses 3s/(s^2-s-6) = 3s/(s-3)(s+2) = A/(s-3) + B/(s+2) = (A(s+2)+B(s-2))/((s-3)(s+2)) Therefore we have A(s+2) +B(s-3) = 3s plugging...

To solve any math question, there may be more than one ways to solve it. 1.79 by 10.5, multiple both of them by 100 which give us 179 by 1050 and then divide it, 179/1050 = 0.17047---

I need help in factoring (answer)

Which question is right (2y)^3+(6y)^2 or 2y^3+6y^2 ? To factor this (2y)^3+(6y)^2 = 2^3 y^3+3^2 2^2 y^2 = 2^2 y^2 (2y+3^2 ) = 4y^2 (2y+9) 2y^3 +6y^2 answered by Nataliya